A cost aware commodity market approach for real-time workload in Hybrid cloud - Ghouchani, Babak Esmaeilpour; Abdullah, Azizol; Abdul Hamid, Nor Asila Wati; Abdul Rahiman, Amir Rizaan (IEEE, 2015)
Cloud computing offers the large scale of computing resources to the customers, and Hybrid cloud computing have large scale heterogeneous resources that are typically owned by different providers while they collaborate with each other. Economic models are a useful solution for offering a bundle of various resources with the best price. It is clear that all the economic models do not provide the same benefits for users in resource utilization. Similarly, the profit earned by Cloud providers as well is different. The existing economic models cannot supply appropriate resources for the Real-time tasks in Hybrid cloud. Therefore, we prepare an enhancement for one of the familiar economic models the commodity market to improve the performance of real-time tasks.